The science of war : Canadian scientists and allied military technology during the Second World War - Avery, Donald, 1938- (University of Toronto Press, 1998)
"The Second World War, with its emphasis on innovative weapons and defence technology, brought about massive changes in the role of scientists in Canada, the United States, and Great Britain. This book explains how and why Canada was able to play in the big leagues of military technology, particularly in the development of radar, RDX explosives, proximity fuses, chemical and biological warfare, and the atomic bomb. It also investigates the evolution of the Canadian national security state, which attempted to protect defence secrets both from the Axis powers and from Canada's wartime ally, the Soviet Union."--Jacket